2011
DOI: 10.1210/jc.2010-1589
|View full text |Cite
|
Sign up to set email alerts
|

The Human Aldose Reductase AKR1B1 Qualifies as the Primary Prostaglandin F Synthase in the Endometrium

Abstract: The human aldose reductase AKR1B1 currently associated with diabetes complications is also a highly functional PGF synthase responsible for PGF2α production in the human endometrium and a potential target for treatment of menstrual disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 42 publications
4
61
0
Order By: Relevance
“…The aldose reductase gene (AKR1B1) encodes the enzyme aldolase reductase responsible for metabolizing progesterone, and is involved in the production of prostaglandin F2α by the endometrium in cattle and humans (Madore et al 2003, Bresson et al 2011. This gene was upregulated in biopsies derived from blastocysts which failed to establish a pregnancy after transfer (El-Sayed et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The aldose reductase gene (AKR1B1) encodes the enzyme aldolase reductase responsible for metabolizing progesterone, and is involved in the production of prostaglandin F2α by the endometrium in cattle and humans (Madore et al 2003, Bresson et al 2011. This gene was upregulated in biopsies derived from blastocysts which failed to establish a pregnancy after transfer (El-Sayed et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that an AKR1C subclass is a PGF synthase responsible for PGF 2a production in the porcine endometrium [9]; however, the expression pattern of this enzyme does not seem to correlate with the levels of uterine endometrial and luminal PGF 2a during the estrous cycle and early pregnancy. Interestingly, recent studies have shown that AKR1B1 is the major PGF synthase responsible for PGF 2a synthesis from PGH 2 in the bovine and human uterine endometrium [24][25][26]. It has been reported that AKR1B1 is expressed in the porcine uterine endometrium, proposing that AKR1B1 may be involved in glucose metabolism [27].…”
Section: Introductionmentioning
confidence: 99%
“…1bed). The status of FP receptor immunoreactivity tended to be correlated with Ki-67 LI (p ¼ 0.0587), but no statistically significant correlations were detected between FP receptor status and any of the clinicopathological parameters (Supplementary Table 2 Previous studies showed that PGF synthases expression levels were altered depending on the menstrual cycle in the endometrium, suggesting that the function or activation of the FP receptor was determined by the expression of these enzymes (Bresson et al, 2011). Therefore, we then immunolocalized currently identified PGF synthases, AKR1C3 and AKR1B1, in the breast cancer tissues detailed above to explore the significance of combined expression of FP receptor and PGF synthase expression.…”
Section: Fp Receptor Expression Had a Trend Towards Association With mentioning
confidence: 98%
“…The antigeneantibody complex was then visualized with 3, 3'-diaminobenzidine (DAB) solution and counterstained with hematoxylin. Normal Endometrium was used as the positive control of immunostaining of PTGFR and AKR1B1 (Dorniak et al, 2011;Bresson et al, 2011), adrenal gland as that of AKR1C3 (Nakamura et al, 2009) and skin epidermis as that of Slug (Mistry et al, 2014).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation